Análise da variabilidade da precipitação e dos processos hidrossedimentológicos na bacia do Alto Rio São Francisco - Beltrão, Joyce de Araujo (2015)
In the contemporary times, there is an expressive concern about systemic management of water resources duo to the imbalance between supply and demand of that good. Hydrological studies about water basin are, mainly aimed at understanding the water balance, the prevailing hydrological processes in the region, the impacts of changes in land use, the quality and quantity of water available for consumption. In this context the goal of this work is to carry out a diagnosis of runoff in the Sub Basin 40 of São Francisco River, located in the Upper São Francisco River region, in order to evaluate the applicability of the model for the area. To assist the analysis, the methodological steps consisted in (1) loading data in SWAT database; (2) definition of the sub basins and creation of hydrological response units (HRU); (3) sensitivity analysis; (4) calibration and validation; (5) simulation and statistical analysis. Were generate 20 sub basins and 190 HRU; the sensitivity analysis showed six parameters more sensitive which, when applied to the model, generated satisfactory results for the calibration and unsatisfactory for some validation periods. In general, the model showed a good efficiency for the simulated events, in spite of some limitations in the related final results primarily in a deficiency observed data for the study of this area of research.